Social Media Addiction in Terms of Gender in Junior High School - Masya, Hardiyansyah; Dewantari, Tri; Meryando, Chika (Psikopedagogia, 2021)
The purpose of this study was to examine the relationship between social media addiction in terms of gender in junior high school students. This research is quantitative research with correlation research type. This study was conducted at SMPN 19 Bandar Lampung, with the research subjects as many as 60 students, 30 male students and 30 female students. Taking the research subject using purposive sampling with the category of students who have an addiction to social media. This study uses a social media addiction scale. Data analysis using phi correlation. The results of this research hypothesis test in 0.05 (0.026> (0.05), which means that there is a correlation between social media addiction in terms of gender. The study results can be used as for guidance and counseling teachers or counselors to provide guidance and counseling services about social media addiction.